Lipid Peroxidation and Serum Total Antioxidant Status in Patients with Recurrent Aphthous Ulceration Treated by Herbal Medicine - N. Hussein, Farhad (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Recurrent aphthous is a common but poorly understood oral mucosal disorder. Impaired oxidant/antioxidant balance is associated with the tissue damage in recurrent aphthous. Aim: To evaluate lipid peroxidation and serum total antioxidant status (TAS) in aphthous patients treated locally by herbal medicine.Patients and methods: Patients were diagnosed and treated for recurrent ulceration in Outpatient Clinic, Mosul, Iraq, from September 2011 to February 2012. A total of 42 patients with recurrent aphthous ulceration (31 males and 11 females) and 25 healthy subjects as controls (19 males and 6 females) were included in the study. The patients were treated with aphthous cream that contained clove, thyme, mint, and liquerice, applied six times daily until cure or for two weeks. The patients were advised to use the cream for two weeks even the aphthous is healed. Blood samples were taken (5 mL) from patients before and after two weeks of treatment and other blood samples from the control group and analyzed for serum malodialdehyde (MDA) and total antioxidant status (TAS) by colorimetric methods. Results: In aphthous patients, serum MDA was significantly higher (p ≤ 0.001) than that in controls (1.82 ± 0.19 vs 1.06 ± 0.12 μmol/L), while serum TAS was significantly lower (p ≤ 0.001) than in the control group (1.16 ± 0.11 vs 1.70 ± 0.16 mmol/L). After treatment, serum MDA was decreased significantly (p ≤ 0.001) compared with the value before treatment (1.82 ± 0.19 vs 1.74 ± 0.17 μmol/L); however, serum TAS was increased significantly (p ≤ 0.05) after treatment compared with the value before treatment (1.16 ± 0.11 vs 1.2 ± 0.08 mmol/L). Both serum MDA and TAS in patients after treatment did not return to the control levels. The aphthous healed in most of the treated patient after 5-7 days, only two patients cured after 10 days of treatment. Conclusion: Aphthous ulceration in patients raises lipid peroxidation and reduces antioxidants. Aphthous treated with cream contained clove, thyme, ment and liquerice, healed within a week and the cured patients were associated with reduced lipid peroxidation and raised antioxidants status.